(untitled) (BIRDEM Medical Journal, 2024)
Background: Aneurysmal bone cyst is a benign, aggressive lesion that occurs in childhood and early adulthood. It usually affects the metaphysis of long bones. The aims of this study were to report clinical and radiological outcome following operative treatment of aneurysmal bone cyst of greater trochanter of femur and asses functional outcome by the Musculoskeletal Tumour Society (MSTS) Rating scale for the lower extremity. Methods: This Quasi-experimental study included 17 patients radiologically and histologically diagnosed as having aneurysmal bone cyst involving the greater trochanter of femur from 2015 to 2022. All cases were curetted, chemical cauterization with 5% phenol done and autogenous cortico-cancellous bone graft were added to fill the osseous defect. The patients were followed-up at 6 weeks and then 3 monthly for 1st year, 6 monthly for 2nd and 3rd year and yearly thereafter. In each follow-up, the recurrence, post-operative complications were documented and MSTS scoring was done. Results: The mean age of the patients were 14.5 years; 9 (53%) were female and 8 (47%) were male. The mean follow-up period for the patients was 3.6 years. There were 3 (18%) recurrences and 2 (11.8%) cases developed superficial surgical site infection. The average MSTS score on final follow-up was 22.6. Conclusion: Aneurysmal bone cyst of the greater trochanter is common in second decade among females. Treatment with extended intralesional curettage, chemical cauterization with 5% phenol and application of autogenous bone graft has less than 18% chance of recurrence. Furthermore, there is acceptable radiological bone graft incorporation and average MSTS score on final follow-up suggest a good functional outcome. BIRDEM Med J 2024; 14(3): 124-130